Strand-Specific RNA Synthesis Determinants in the RNA-Dependent RNA Polymerase of Poliovirus - Cornell, Christopher T. (J Virol, 2004)
The viral RNA-dependent RNA polymerase (3D(pol)) is highly conserved between the closely related enteroviruses poliovirus type 1 (PV1) and coxsackievirus B3 (CVB3). In this study, we generated PV1/CVB3 chimeric polymerase sequences in the context of full-length poliovirus transcripts to determine the role of different subdomains within the RNA-dependent RNA polymerase of PV1 that are required for functions critical for RNA replication in vitro and in cell culture. The substitution of CVB3 sequences in the carboxy-terminal portion (thumb subdomain) of the polymerase resulted in transcripts incapable of RNA replication. In contrast, three of the seven chimeras were capable of synthesizing RNA, albeit to reduced levels compared to that of wild-type PV1 RNA. Interestingly, one of the replication-competent chimeras (CPP) displayed an inability to generate positive strands, indicating the presence of amino-terminal sequences within the 3D polymerase and/or the 3D domain of the 3CD precursor polypeptide that are necessary for the assembly of strand-specific RNA synthesis complexes. In some constructs, the partial reestablishment of PV1 amino acid sequences in this region was capable of rescuing RNA replication in vitro and in cell culture.